PEMANFAATAN LIMBAH DAUN KERING DAN KERTAS DAUR ULANGSEBAGAI BAHAN DASAR PEMBUATAN SCRAPBOOK - Untung Kurniawan dan Agus Wakhid (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research aims to know the process and feasibility of making scrapbook usingdry leaves and recycled paper. By using these two materials, it can be produced thelatest breakthrough with high art value and low price.The tools used in this prosess were stationery, ruler, brush, iron, scissors, andcutter while the materials were dry leaves, clean water, varnish, thiner, white glue ( woodglue), cardboard paper, carton, recycled paper, and natural additional widgets. Thisprocess followed some following steps: 1) collecting basic materials and tools, 2) initialcleaning, 3) determining theme, 4) forming and designing the cover, 5) forming pagesfrom recycled paper, 5) designing widgets from dry leaves, 6) arranging, 7) lacquering,and 9) testing the feasibility .The result of the research shows that the making of scrapbook as the handcraftusing recycled paper and dry leaves based on the feasibility procentage from experts ofhandiraf product is 82,8%). Meanwhile, the respond from societies who prefer the naturaldesign to made design is about 74% . This is an opportunity for marketing this product.Key words: scrapbook, dry leaves, recycled paper